'You can't feel what we feel': Multifaceted dyspnoea invisibility in advanced chronic obstructive pulmonary disease examined through interpretative phenomenological analysis. (October 2022) - Serresse, Laure; Guerder, Antoine; Dedonder, Jonathan; Nion, Nathalie; Lavault, Sophie; Morélot-Panzini, Capucine; Gonzalez-Bermejo, Jésus; Benoit, Laelia; Similowski, Thomas
Background: More than a symptom, dyspnoea is an existential experience shaping the lives of those afflicted, particularly when its persistence despite maximal pathophysiological treatments makes it pervasive. It is, however, insufficiently appreciated by concerned people themselves, family members, healthcare professionals and the public (dyspnoea invisibility), limiting access to appropriate care and support. Aim: To provide a better understanding of dyspnoea experiences and its invisibility. Design: Interpretative phenomenological analysis of data collected prospectively through in-depth semi-structured interviews. Setting/Participants: Pulmonary rehabilitation facility of a tertiary care university hospital; 11 people (six men, five women) with severe chronic obstructive pulmonary disease (stages 3 and 4 of the 4-stage international GOLD classification) admitted for immediate post-exacerbation rehabilitation. Results: We identified several types of dyspnoea invisibility depending on temporality and interlocutors: (1) invisibility as a symptom to oneself; (2) invisibility as a symptom to others; (3) invisibility as an experience that cannot be shared; (4) invisibility as an experience detached from objective measurements; (5) invisibility as an experience that does not generate empathic concern. The notion of invisibility was present in all the identified experiential dimensions of dyspnoea. It was seen as worsening the burden of the disease and as self-aggravating through self-isolation and self-censorship. Conclusions: The study confirmed that dyspnoea invisibility is a reality for people with advanced chronic obstructive pulmonary disease. It shows dyspnoea invisibility to be a multifaceted burden. Future research should aim at identifying individual and collective measures to overcome dyspnoea invisibility.